2018
DOI: 10.1016/j.ejphar.2018.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of peptidylarginine deiminase alleviates LPS-induced pulmonary dysfunction and improves survival in a mouse model of lethal endotoxemia

Abstract: Immune cell death caused by neutrophil extracellular traps (NETs), referred to as NETosis, can contribute to the pathogenesis of endotoxemia and organ damage. Although the mechanisms by which infection induces NETosis and how that leads to organ dysfunction remain largely unknown, NET formation is often found following citrullination of histone H3 (CitH3) by peptidylarginine deiminase (PAD). We hypothesized that lipopolysaccharide (LPS)-induced activation of PAD and subsequent CitH3-mediated NET formation incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 34 publications
0
55
0
Order By: Relevance
“…After validation of the CitH3 mAb (4 Cit), we evaluated whether the new antibody could improve survival in a mouse model of LPS-induced endotoxic shock. It has been shown previously that CitH3 appears within 30 min of endotoxic shock (18,23). In the present study, mice were intravenously administrated anti-CitH3 mAb immediately after LPS injection.…”
Section: The Cith3 Mab (4 Cit) Improves Survival Compared To Cith3 Mamentioning
confidence: 74%
See 3 more Smart Citations
“…After validation of the CitH3 mAb (4 Cit), we evaluated whether the new antibody could improve survival in a mouse model of LPS-induced endotoxic shock. It has been shown previously that CitH3 appears within 30 min of endotoxic shock (18,23). In the present study, mice were intravenously administrated anti-CitH3 mAb immediately after LPS injection.…”
Section: The Cith3 Mab (4 Cit) Improves Survival Compared To Cith3 Mamentioning
confidence: 74%
“…Unlike histones, the role of citrullinated histones in diseases remains largely unknown. CitH3 release has been detected in blood and peritoneal fluid in sepsis (17,18,23); however, the effects of CitH3 production and its pathophysiologic roles in sepsis are unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, arginine residues on histones H3 and H4 may undergo deimination by peptidyl deiminase 4 (PAD4) in neutrophils, converting arginine to citrulline which facilitates chromatin decondensation during NET formation [ 51 ]. Moreover, citrullinated histones are found in the extracellular space as the most abundant protein component of NETs [ 52 , 53 ]. Previous studies from our laboratory demonstrated that recombinant citrullinated histone 3 (CitH3) caused plasma leakage in the splanchnic microcirculation and promoted endothelial AJ opening via contractile cytoskeleton reorganization [ 54 ].…”
Section: Discussionmentioning
confidence: 99%